Buccal swab: A tissue sampling method for refinement of experimental procedures involving rainbow trout. (11th March 2017) - Colussi, S.; Campia, V.; Righetti, M.; Scanzio, T.; Riina, M. V.; Burioli, E. A. V.; Foglini, C.; Ingravalle, F.; Prearo, M.; Acutis, P. L.
Summary: Buccal swabbing is a minimally invasive method to obtain DNA and biological material from humans and animals, including fish. Reports on buccal swabbing in fish are few and only for a limited number of species. Rainbow trout ( Oncorhynchus mykiss ) is an important animal model and because the yield of DNA may vary among and within different species in individuals of different sizes, it was selected as useful to optimize the buccal DNA collection in this species. Different storage methods were evaluated, aimed at DNA preservation by limiting DNA degradation and bacterial growth, using commonly available and inexpensive reagents. DNA quality was also tested by amplification of a single‐copy nuclear gene and a mitochondrial gene. The results suggest that ethanol is the best storage choice for buccal swab sampling in fish genetic studies, as well as suitable for small‐bodied rainbow trout.